ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI NUSA TENGGARA DAN PAPUA - Ni Nyoman Yuliarmi, I Nyoman Giriadi Saputra, (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 12 (2020): VOL 9 NO 12, DESEMBER 2020 (2618-2851), 2020)
ABSTRACT This study aims (1) to analyze the effect of gross regional domestic product, unemployment rate, investment and inflation simultaneously on poverty in Nusa Tenggara and Papua, (2) to analyze the effect of gross regional domestic product, unemployment rate, investment, and inflation simultaneously. partial to poverty in Nusa Tenggara and Papua. (3) to determine the role of inflation in moderating the effect of investment on poverty in Nusa Tenggara and Papua. This research was conducted in Nusa Tenggara and Papua using three provinces as observation points with a time span from 2007 to 2018 with a large sample size of 36 observations with the analytical technique method used in this study is moderation regression analysis. The results of partial data analysis show ( 1) Gross Regional Domestic Product has a negative and significant effect on the poverty level, unemployment partially has a negative and significant effect on the poverty level. (2) Partial investment has a positive and significant effect on the poverty level (3) Inflation partially has a negative and significant effect on the poverty level. (4) Inflation moderates the effect of investment on poverty levels in Eastern Indonesia. Keywords: gross regional domestic product, unemployment, investment, inflation, poverty level